Physical therapy clinical specialization and management of red and yellow flags in patients with low back pain in the United States - Ladeira, Carlos E. (J Man Manip Ther, 2018)
OBJECTIVES: Physical therapists (PTs) may practice in direct access or act as primary care practitioners, which necessitate patients’ screening and management for red, orange and yellow flags. The objective of the project was to assess the American PT’s ability to manage red, orange and yellow flags in patients with low back pain (LBP), and to compare this ability among PTs with different qualifications. METHODS: The project was an electronic cross-sectional survey. The investigators contacted 2,861 PTs. Participants made clinical decisions for three vignettes: LBP with red flag for ectopic pregnancy, with orange flag for depression and with yellow flag for fear avoidance behaviour (FAB). The investigators used logistic regression to compare management of warning flags among PTs with distinct qualifications: orthopaedic clinical specialists (PTOs), fellows of the AAOMPT (PTFs), PTOs and PTFs (PTFOs), and PTs without clinical specialization (PTMSs). RESULTS: A total of 410 PTs completed all sections of the survey (142 PTOs, 110 PTFOs, 74 PTFs and 84 PTMSs). Two hundred and seventeen PTs (53%) managed the patient with LBP and symptoms of ectopic pregnancy correctly, 115 PTs (28.5%) of them managed the patient with LBP and symptoms of depression correctly, and 177 (43.2%) managed the patient with LBP and FAB correctly. DISCUSSION: In general, PTs with specialization performed significantly better than PTMSs in all three clinical vignettes. PTs ability to manage patients with warning flags was relatively low. Based on our results, further education on patients with LBP and warning flags is needed. The survey had the potential for non-response and self-selection bias. LEVEL OF EVIDENCE: 3b.